Microbial identification from faces and urine in one step by two-photon excitation assay technique - Juha M. Koskinen; Jori M.Soukka; Niko J.Meltola; Janne O.Koskinen (ELSEVIER SCIENCE BV, 2022)
Two-photon excitation fluorometry (TPX) is a separation-free bioaffinity assay technique which enables accurate diagnostic testing in microvolumes. The technology is currently commercially applied in an automated mariPOC (R) test system for rapid phenotypic multi-microbe detection of pathogen antigens. The first TPX applications for diagnostics were intended for respiratory infection testing from nasopharyngeal and oropharyngeal samples. Feces and urine are more complex sample matrices and contain substances that may interfere with immunoassay binding or fluorescence detection. Our objective was to study the suitability of these complex matrices in the TPX technique. As expected, feces and urine elevated fluorescence levels but the methodology has the unique property of compensating for matrix effects. Compensation allows reliable separation of specific fluorescence from the fluorescence caused by the matrix. The studied clinical samples did not contain immunoassay inhibitors. The results suggest that the methodology is robust and may provide reliable testing of feces and urine samples with high accuracy.